2023
DOI: 10.3389/fendo.2022.1083690
|View full text |Cite
|
Sign up to set email alerts
|

Graves disease is more prevalent than Hashimoto disease in children and adolescents with type 1 diabetes

Abstract: IntroductionAutoimmune thyroid disease (AITD) is the most common associated autoimmune disorder in type 1 diabetes (T1D). Early detection of AITD is crucial to optimize glycemic control, growth, and intellectual development. In this prospective cohort study, we sought to characterize the prevalence, incident ages and risk factors of AITD in children and adolescents with T1D.Materials and methodsPatients with T1D diagnosed at ≤ 18 years at MacKay Children’s Hospital, Taipei, from 1990 to 2019 underwent annual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
1
1
Order By: Relevance
“…In contrast to our ndings, the results of observational studies indicated that AITD is the most prevalent comorbid autoimmune condition in T1DM [34]. Further, GD increases the rate of neuropathy [35].…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our ndings, the results of observational studies indicated that AITD is the most prevalent comorbid autoimmune condition in T1DM [34]. Further, GD increases the rate of neuropathy [35].…”
Section: Discussioncontrasting
confidence: 99%
“…Thyroid disorders are among the most frequent endocrinological disorders recognized in the pediatric age groups, with an overall incidence of autoimmune hypothyroidism of 1%-3% in the United States, which is overall significantly more frequent than hyperthyroidism, which constitutes only 15% of children's thyroid disorders [21]. However, in a cohort of 808 patients in Taiwan, 4.1% of patients developed Graves' disease compared to 1.4% of patients who had Hashimoto disease [19].…”
Section: Common Comorbidities Of T1dmentioning
confidence: 99%